The taking - Koontz, Dean R. (Dean Ray), 1945- (Bantam Books, 2004)
Molly and Niel Sloan awake to see golden rain falling. In their remote California mountain town, they learn from their television of enormous waterspouts and blizzards around the globe; then, the television ceases, as do all other forms of communication with the outside world. The Sloans are left, together with their neighbors, in the midst of a purple fog, disturbed by a threat they cannot identify or understand. Together they discover that the world is being prepared for beings other than themselves--beings with vast technological powers at their disposal, who will stop at nothing to hunt them down and kill them all.